Morphological plasticity of endophytic Chitinophaga pinensis - Janine Liedtke; Frans Rodenburg; Chao Du; Le Zhang; Jos M. Raaijmakers; Gilles P. van Wezel; Ariane Briegel (Antonie van Leeuwenhoek, 2026)
Environmental changes, whether due to climate change or human influences, compromise the resilience of plants to biotic and abiotic stresses, such as pathogens, drought and heat. Plant microbiota are known to promote plant resilience. To be able to harness the power of the plant microbiome we need to identify microbiota with health-promoting properties. Recent studies have demonstrated that the bacterium Chitinophaga pinensis enhances plant health and increases resistance to fungal infections. Here, we show that C. pinensis exhibits an unusually high morphological plasticity, switching between a filamentous and a spherical cell state, each of which is characterized by a distinct transcriptional profile. Despite these transcriptional differences, spherical cells remained metabolically active and replicating, while lacking structural characteristics typically associated with dormant states. Furthermore, the spherical cell morphology of C. pinensis facilitates hitchhiking behaviour and motility via surfactin cheating, potentially influencing its dispersal and interactions within the plant microbiome. To investigate the structural dynamics and transcriptional adaptation of this plant endophyte, we applied a combination of microscopy and culture-based techniques. Taken together, our study provides new insights into the morphological flexibility and transcriptional regulation of the plant-beneficial C. pinensis .

Wastewater-based surveillance of SARS-CoV-2: Short-term projection (forecasting), smoothing and outlier identification using Bayesian smoothing - Douglas G. Manuel; Gauri Saran; Ivan Lee; Warsame Yusuf; Mathew Thomson; Élisabeth Mercier; Vince Pileggi; R. Michael McKay; Ryland Corchis-Scott; Qiudi Geng; Mark Servos; Heather Ikert; et al. (Science of The Total Environment, 2024)

Source Apportionment of Polychlorinated Biphenyls in Atmospheric Deposition in the Seattle, WA, USA Area Measured with Method 1668 - Lisa A. Rodenburg; Iris Winstanley; Jennifer M. Wallin (Archives of Environmental Contamination and Toxicology, 2019)

Mutated PET117 causes complex IV deficiency and is associated with neurodevelopmental regression and medulla oblongata lesions - G. H. Renkema; G. Visser; F. Baertling; L. T. Wintjes; V. M. Wolters; J. van Montfrans; G. A. P. de Kort; P. G. J. Nikkels; P. M. van Hasselt; S. N. van der Crabben; R. J. T. Rodenburg (Human Genetics, 2017)

A day and night difference in the response of the hepatic transcriptome to cyclophosphamide treatment - Kirsten C. G. Van Dycke; Romana M. Nijman; Paul F. K. Wackers; Martijs J. Jonker; Wendy Rodenburg; Conny T. M. van Oostrom; Daniela C. F. Salvatori; Timo M. Breit; Harry van Steeg; Mirjam Luijten; Gijsbertus T. J. van der Horst (Archives of Toxicology, 2015)

Insulin and Chromium Picolinate Induce Translocation of CD36 to the Plasma Membrane Through Different Signaling Pathways in 3T3-L1 Adipocytes, and with a Differential Functionality of the CD36 - Yiqun Wang; Masja M. Van Oort; Minghui Yao; Dick J. Van der Horst; Kees W. Rodenburg (Biological Trace Element Research, 2011)

CO2-assimilation and chlorophyll fluorescence as indirect selection criteria for host tolerance against Striga - Jonne Rodenburg; Lammert Bastiaans; Ad. H. C. M. Schapendonk; Peter E. L. van der Putten; Aad van Ast; Niels J. Dingemanse; Bettina I. G. Haussmann (Euphytica, 2008)

Effects of Ca- and Fe-rich Seepage on P Availability and Plant Performance in Calcareous Dune Soils - C. Bakker; J. Rodenburg; P. M. van Bodegom (Plant and Soil, 2005)

Endotoxin-induced liver damage in rats is minimized by 2 -adrenoceptor stimulation - A. S. van Miert; R. R. Witkamp; R. J. T. Rodenburg; C. A. Izeboud; K. H. N. Hoebe; A. F. Grootendorst; S. M. Nijmeijer (Inflammation Research, 2004)

Thresholds for the perception of rotation: Variability, psychometric curves, and comparison with hearing thresholds - M. Rodenburg; A. J. J. Maas; H. P. W. Stassen (Biological Cybernetics, 1981)

The threshold of perception of angular acceleration as a function of duration - M. Rodenburg; H. P. W. Stassen; A. J. J. Maas (Biological Cybernetics, 1981)